Recurrent Pneumonia due to Fibrosing Mediastinitis in a Teenage Girl: A Case Report with Long-Term Follow-Up. (18th March 2018) - Hevroni, Avigdor; Springer, Chaim; Wasser, Oren; Avital, Avraham; Koplewitz, Benjamin Z.
Abstract : A teenage girl was evaluated for recurrent right pneumonia. The evaluation revealed a calcified mediastinal mass that compressed the right intermediate and middle lobar bronchi, as well as the right pulmonary artery and veins. The clinical picture together with imaging studies and borderline positive serology testing suggested a diagnosis of fibrosing mediastinitis associated with histoplasmosis. This rare condition is characterized by the local proliferation of invasive fibrous tissue within the mediastinum due to a hyperimmune reaction to Histoplasma capsulatum . Antifungal and anti-inflammatory therapies are usually ineffective, and surgical intervention contains a high morbidity risk. Palliative surgery and stenting of the compressed airway have been suggested. In the past, the prognosis was thought to be poor, but recent studies demonstrate a more positive outcome. Our patient had been radiologically and functionally stable under follow-up for over thirteen years and has married and delivered two healthy children, both following an uneventful pregnancy.